World Bank Research Digest, Vol. 3(1) - World Bank (Washington, DC, 2014)
In this issue: food price crisis in Africa; focus: the Doha development agenda; when is deposit insurance a good idea? Returns to capital in micro-enterprises; new global poverty estimates; ports and maritime transport in West and Central Africa; the consequences of child labor; and gender and asset ownership.